Effect of Agitation Speed and Cultivation Time on the Production of the Emestrin Produced by Emericella nidulans Marine Fungal - muhammad nursid nursid; Martua Manulang; Joko Samiadji; Endar Marraskuranto (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2015)
Emestrin, an epipolythidioxopiperazine (EPT), is bioactive secondary metabolite produced by the marine fungus Emericella nidulans. Emestrin is potential to be developed as anticancer agent. Our present study investigated the effect of the agitation speed and cultivation time on the production of the mycelial biomass and emestrin in E. nidulans. The fungal was cultivated in malt extract broth (MEB) medium with varying agitation speeds of 0, 50, 100,150 rpm during 1,2,3 and 4 weeks of incubation at the temperature of 28 oC. Concentration of emestrin was determined by using high performed liquid chromatography (HPLC). The highest concentration of emestrin was found at static condition (0 rpm) cultivated for 1 week.